The Effect of TikTok Shop Impulse Buying On The Fashion Product Consumption Behavior Of Female Students At Smk Negeri 2 In Cirebon City - Arguna Arguna; Farida Nurfalah (ann4publisher@gmail.com, 2026)
Background. Adolescent consumption patterns are influenced by the rise of social media platforms, such as TikTok Shop, which combine entertainment and shopping on a single platform. Aims. This study investigates the impact of impulse buying on TikTok Shop on the fashion consumption behavior of female students at SMK Negeri 2 in Cirebon City. Methods. The study employed a quantitative method and involved 77 respondents, selected using the Slovin formula with a 10% margin of error. Data were collected via a Likert-scale questionnaire and analyzed using SPSS 2023 through validity, reliability, normality, linearity, and simple linear regression tests. Result. The analysis results indicate that impulse buying has a significant influence on consumption behavior. This means that the higher the students’ tendency to make impulsive purchases, the higher their consumption behavior. There is a significant and positive relationship between the tendency toward impulse buying and the students’ consumer behavior, with a correlation coefficient (R) of 0.548 and a coefficient of determination (R²) of 0.301. This implies that a one-unit increase in impulse buying will increase consumer behavior by 0.451, in accordance with the regression equation Y = 7.621 + 0.451X. Conclusion. The results of this study are expected to help parents, educators, and digital marketers understand how social media, particularly TikTok, influences adolescent consumption behavior. Implementation. These findings can also serve as a reference for teaching adolescents about financial literacy and how to exercise self-control while shopping in the internet age.